1997
DOI: 10.1128/mcb.17.11.6311
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Enriched Transcription Factors Uncoupled from Expression of Hepatic Functions in Hepatoma Cell Lines

Abstract: Among the liver-enriched transcription factors identified to date, only expression of hepatocyte nuclear factor 4 (HNF4) and hepatocyte nuclear factor 1 (HNF1) is in strict correlation with hepatic differentiation in cultured rat hepatoma cells. Indeed, differentiated hepatoma cells that stably express an extensive set of adult hepatic functions express liver-enriched transcription factors, while dedifferentiated cells that have lost expression of all these hepatic functions no longer express HNF4 and HNF1. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…The M29 cells have a phenotype similar to cells reported by Chaya et al [58], in which a hepatoma derived cell line showed that liver gene expression appeared to be uncoupled from expression of HNF4 and HNF1a. Specifically, liver gene expression ceased despite the presence of HNF4 and HNF1a.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The M29 cells have a phenotype similar to cells reported by Chaya et al [58], in which a hepatoma derived cell line showed that liver gene expression appeared to be uncoupled from expression of HNF4 and HNF1a. Specifically, liver gene expression ceased despite the presence of HNF4 and HNF1a.…”
Section: Discussionsupporting
confidence: 62%
“…The third class of cells described by Weiss et al were chromosomally reduced hepatoma x fibroblast hybrid cells in which the liver phenotype could be completely rescued with the introduction of either HNF4 or HNF1a [58]. This in contrast to karyotypically complete cell hybrids, which are refractory to activation by the introduction of transacting factors with the exception that HNF4 rescued HNF1a expression (but not downstream HNF1a-responsive genes) [8].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…25 However, DEX can inhibit apoptosis in some cells such as neutrophils and tumors. 6,12,26 The antiapoptotic effect by DEX has been shown to be due to the upregulation of the Bcl-2 family proteins such as Bcl-2 and Bcl-xL in hepatocytes. 8 These protein levels have been shown to be upregulated in hepatocytes only after long-term treatment with DEX Figure 6 Pretreatment with DEX protects hepatocytes from Jo2-induced apoptosis by inhibiting DISC formation and caspase-8 activation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HNF-4 (28) is a major activator of the gene encoding HNF-1␣ (29,30), a member of the HNF-1 family (31-33), and HNF-1␣ itself activates expression of more than 20 liver genes, including ␣1-antitrypsin (␣1AT, gene symbol PI) (34,35). The expression patterns of HNF-1␣ and HNF-4 closely correlate with the differentiated state of cultured hepatic cells, and studies using dedifferentiated hepatoma variants, transactivator-deficient hepatoma variants, and somatic cell hybrids have suggested that the HNF-4͞HNF-1␣ activation pathway is involved in both the determination and maintenance of hepatic phenotype (30,(35)(36)(37)(38)(39)(40).…”
mentioning
confidence: 99%